Trend of Realistic Mathematics Education Research on Indonesian Elementary Schools between 2013 and 2022 - Kurnaedi, Eko Pradipta; Murti, Rahayu Condro; Afifah, Nur (Universitas Pendidikan Ganesha, 2024)
Research on Realistic Mathematics Education or RME is one of the most widely conducted for mathematics subjects, specifically in Indonesia. This study aims to analyze the articles on RME topics in Indonesian elementary schools between 2013 and 2022. This study employed a qualitative approach using a content analysis method. This study has found that the number of publications on RME topics in Indonesian elementary schools has fluctuated between 2013 and 2022. There were 155 Sinta-accredited, even Scopus-indexed journals with 265 articles published. Java was the location of the majority of research. Among hundreds of publications, quantitative research was mostly found. In addition, the majority of the research subjects were fifth-grade students. The most frequently examined research object is learning outcome. Measurement and geometry were the most chosen topic in research. Test was the most commonly used data collection technique, and percentage was the most frequently used data analysis method. Several recommendations are included as implications of this study. The source of data and the range of publication years are limitations of this study.